Safety, tolerability, and biomarkers of the treatment of mice with aerosolized toll-like receptor ligands - Alfaro, Victoria; Goldblatt, David L.; Valverde, Gabriella R.; Munsell, Mark; Quinton, Lee J.; Walker, Adam K.; Dantzer, Robert; Varadhachary, Atul; Scott, Brenton L.; Evans, Scott E.; Tuvim, Michael J.; Dickey, Burton F. (Frontiers in Pharmacology, 2014)
We have previously discovered a synergistically therapeutic combination of two Toll-like receptor (TLR) ligands, an oligodeoxynucleotide (ODN) and Pam2CSK4. Aerosolization of these ligands stimulates innate immunity within the lungs to prevent pneumonia from bacterial and viral pathogens. Here we examined the safety and tolerability of this treatment in mice, and characterized the expression of biomarkers of innate immune activation. We found that neutrophils appeared in lung lavage fluid 4 hours after treatment, reached a peak at 48 hours, and resolved by 7 days. The peak of neutrophil influx was accompanied by a small increase in lung permeability. Despite the abundance of neutrophils in lung lavage fluid, only rare neutrophils were visible histopathologically in the interstitium surrounding bronchi and veins and none were visible in alveolar airspaces. The cytokines IL-6, TNF and CXCL2 rose several hundred-fold in lung lavage fluid 4 hours after treatment in a dose-dependent and synergistic manner, providing useful biomarkers of lung activation. IL-6 rose five-fold in serum with delayed kinetics compared to its rise in lavage fluid, and might serve as a systemic biomarker of immune activation of the lungs. The dose-response relationship of lavage fluid cytokines was preserved in mice that underwent myeloablative treatment with cytosine arabinoside to model the treatment of hematologic malignancy. There were no overt signs of distress in mice treated with ODN/Pam2CSK4 in doses up to 8-fold the therapeutic dose, and no changes in temperature, respiratory rate, or behavioral signs of sickness including sugar water preference, food disappearance, cage exploration or social interaction, though there was a small degree of transient weight loss. We conclude that treatment with aerosolized ODN/Pam2CSK4 is well tolerated in mice, and that innate immune activation of the lungs can be monitored by the measurement of inflammatory cytokines in lung lavage fluid and serum.